Does trade performance say anything about efficient industrialization policies? Some evidence from Pacific Rim Countries - Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
Throughout mainstream economic development literature and, in particular, the analysis of international trade performance, references to the importance of allowing factor prices in a given land to reflect the relative scarcity of its factors of production abound. The consequences for developing countries (DCs) of specialization in the production of goods using more of the factors of production, with which they are better endowed, are stated to be a more efficient economy, which provides the basis for faster growth and a higher degree of competitiveness in world markets. That is to say, in countries with highly distorted factor (and product) markets economic development will be hampered or rather the degree of competitiveness in world markets will be negatively influenced. Notwithstanding the fundamental implications of the impact of domestic market distortions on performance in world trade for development policy recommendations, Krueger (1984, p. 555) notes that relatively little empirical work has been undertaken to estimate their magnitude or their affects. It is the latter aspect which is dealt with in this paper, namely the impact of distortions on the performance of countries in world trade with particular reference paid to Pacific Rim (PACRIM) Countries. Specifically, it intends to yield evidence on the relevance of ensuring that, in particular, domestic factor markets are relatively free from those influences (i.e. policy measures) which cause production to be shifted out of areas of comparative advantage.
Keywords: 330; Außenwirtschaft; Industrialisierung; Arbeitsmarkt; Finanzmarkt; Pazifischer Raum